Obligatory Role for B Cells in the Development of Angiotensin II–Dependent Hypertension. Issue 5 (November 2015) - Chan, Christopher T.; Sobey, Christopher G.; Lieu, Maggie; Ferens, Dorota; Kett, Michelle M.; Diep, Henry; Kim, Hyun Ah; Krishnan, Shalini M.; Lewis, Caitlin V.; Salimova, Ekaterina; Tipping, Peter; Vinh, Antony; et al.
Abstract : Clinical hypertension is associated with raised serum IgG antibodies. However, whether antibodies are causative agents in hypertension remains unknown. We investigated whether hypertension in mice is associated with B-cell activation and IgG production and moreover whether B-cell/IgG deficiency affords protection against hypertension and vascular remodeling. Angiotensin II (Ang II) infusion (0.7 mg/kg per day; 28 days) was associated with (1) a 25% increase in the proportion of splenic B cells expressing the activation marker CD86, (2) an 80% increase in splenic plasma cell numbers, (3) a 500% increase in circulating IgG, and (4) marked IgG accumulation in the aortic adventitia. In B-cell–activating factor receptor–deficient (BAFF-R −/− ) mice, which lack mature B cells, there was no evidence of Ang II–induced increases in serum IgG. Furthermore, the hypertensive response to Ang II was attenuated in BAFF-R −/− (Δ30±4 mm Hg) relative to wild-type (Δ41±5 mm Hg) mice, and this response was rescued by B-cell transfer. BAFF-R −/− mice displayed reduced IgG accumulation in the aorta, which was associated with 80% fewer aortic macrophages and a 70% reduction in transforming growth factor-β expression. BAFF-R −/− mice were also protected from Ang II–induced collagen deposition and aortic stiffening (assessed by pulse wave velocity analysis). Finally, like BAFF-R deficiency, pharmacological depletion of B cells with an anti-CD20 antibody attenuated Ang II–induced hypertension by ≈35%. Hence, these studies demonstrate that B cells/IgGs are crucial for the development of Ang II–induced hypertension and vessel remodeling in mice. Thus, B-cell–targeted therapies—currently used for autoimmune diseases—may hold promise as future treatments for hypertension. Abstract : Supplemental Digital Content is available in the text.